Effects of varying material properties on the vibro-acoustic and tonal quality of classical guitar - Lucas, Crisron Rudolf G.
A recent project entitled Gitara Ni Juan has already tried to use modern physical modeling techniques to guide the Filipino luthiers in wood selection process and to give them idea of the sound quality that specific types of wood will produce given a fixed guitar geometry. However, the model is still incomplete as the research has not yet completely determined the effects of changing the wood to the sound properties of the guitar. Moreover, digital sound synthesis using FEM from the complete system of air, body and string has not yet been done even in recent literature. With that in mind, the objective of this study is to establish an FEM model that can 1) synthesize the guitar sound, 2) simulate the vibro-acoustic properties of different materials, and 3) relate it to the psychoacoustic features such as brightness. In this thesis, the effects of varying the wood materials on the vibration modes, acoustic, and psychoacoustic features of the coupled system of guitar body, air, and string are discussed and analyzed. Four main properties were examined: 1) Density, 2) Young's Modulus, 3) Shear Modulus and 4) Poisson's Ratio. Using the geometry used in Gitara Ni Juan, a 3D model was designed in COMSOL Multiphysics. Modal characteristics as well as Frequency and Transient characteristics are observed. Results show that 1) Density is inversely proportional to the shift in the frequency response and mode frequencies while 2) the Young's Modulus, Shear Modulus and Poisson Ratio are directly proportional to the shift in frequency response. Higher frequency modes are more affected by Density, and Poisson Ratio as indicated by the larger slopes. The change in frequency per mode with respect to material parameters was observed to be linear. However, the slope is not constant for all modes and still varies depending on the mode frequency. For the Brightness test, ranking of the actual test is consistent with MIR Brightness for cut-off frequencies around 150-300 Hz. Brightness is inversely proportional with density and directly proportional to Young's modulus, Shear modulus and Poisson Ratio. Novel contribution of this research is a multi-physics model that can digitally synthesize a sound from the coupled air, body and string parameters. Also, the linkage of the elastic properties has been related to the brightness. For future work, the improvement of the model and the listening test is suggested. Also, collection of actual wood data from Gitara Ni Juan is suggested to compare the multiphysics model with actual classical guitars.